Pengaruh Beban Kerja, Lingkungan Kerja dan Job Insecurity terhadap Turnover Intention - Arrad, Adya Laksmi; Tjahjadi, Karel (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to analyze and determine the effect of work load, work environment, and job insecurity on turnover intention of employees at PT. X. The population used in this study were employees of PT. X as many as 66 employees. The sampling technique used is saturation sampling where all the employees in the population is used as a sample. The sample is 66 employees of PT. X. The technique of collecting data is by distributing questionnaires using a Likert scale. The data were then analyzed using multiple linear regression. Based on the results of the analysis of hypothesis testing data in this study, it shows that workload has an effect on turnover intention, work environment has no effect on turnover intention, and job insecurity has no effect on turnover intention.